A quantitative systematic review of the efficacy of mobile phone interventions to improve medication adherence. (1st April 2014) - Park, Linda G.; Howie‐Esquivel, Jill; Dracup, Kathleen
Abstract Aims To evaluate the characteristics and efficacy of mobile phone interventions to improve medication adherence. Secondary aims are to explore participants' acceptability and satisfaction with mobile phone interventions and to evaluate the selected studies in terms of study rigour, impact, cost and resource feasibility, generalizability and implications for nursing practice and research. Background Medication non‐adherence is a major global challenge. Mobile phones are the most commonly used form of technology worldwide and have the potential to promote medication adherence. Design Guidelines from the Centre for Reviews and Dissemination were followed for this systematic review. Data Sources A comprehensive search of databases (PubMed, Web of Science, CINAHL, PsycInfo, Google Chrome and Cochrane) and bibliographies from related articles was performed from January 2002–January 2013 to identify the included studies. Review Methods A quantitative systematic review without meta‐analysis was conducted and the selected studies were critically evaluated to extract and summarize pertinent characteristics and outcomes. Results The literature search produced 29 quantitative research studies related to mobile phones and medication adherence. The studies were conducted for prevention purposes as well as management of acute and chronic illnesses. All of the studies used text messaging. Eighteen studies found significant improvement in medication adherence. Conclusion While the majority of investigators found improvement in medication adherence, long‐term studies characterized by rigorous research methodologies, appropriate statistical and economic analyses and the test of theory‐based interventions are needed to determine the efficacy of mobile phones to influence medication adherence.